Ekonomiczne, społeczne i ekologiczne problemy związane z wykorzystaniem biopaliw - Kociszewski, Karol (Economic, Social and Environmental Problems Connected with the Use of Biofuels, 2009)
The increase of biofuels production, which is presently observed, is initiated by policy aimed at reducing two important problems of the world's economy - global climate changes and fuel markets crisis. In that context, the paper identifies and characterizes economic, social and environmental hazards connected with biofuels use. Its objective is pointing out the problems in the aspect of policy supporting biofuels production legitimacy. The presented arguments can prove that there is a need for the policy change but it does not mean that it should be completely abandoned. It is proposed to develop second-generation biofuels production. It could help to reduce the phenomenon of competition between agricultural resources use for food and biofuels production.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 264-272